The effect of hemostatic agents and dentin cleansing protocols on shear bond strength of resin composite using universal adhesive: an in vitro study - Manar M. Abu-Nawareg; Maher S. Hajjaj; Tariq S. AbuHaimed; Reem A. Ajaj; Roaa Abuljadayel; Yousef AlNowailaty; Arwa Alnoury; Naseeba Khouja; Ghada H. Naguib; Saeed J. Alzahrani; Dalia A. Abuelenain (BMC, 2024)
Abstract Background During restoring class II and V cavities with resin composite, hemostatic agents are frequently used to control gingival bleeding and/or gingival fluid to provide a dry field which is crucial for efficient bonding. Hemostatic agents may adversely affect the bonding procedure, thus their removal prior to bonding is essential. The current study evaluates the effect of two hemostatic agents and different dentin cleansing protocols on the shear bond strength of resin composite to dentin using a universal adhesive. Methods Ninety premolars were sectioned to expose coronal dentinal surfaces which were divided into 3 groups: control group, not treated with hemostatic agent (n = 10); a group treated with Viscostat "20% ferric sulphate" (n = 40); and a group treated with Viscostat clear "25% aluminum chloride" (n = 40). The groups treated with hemostatic agents were subdivided into 4 subgroups according to the cleansing protocol: water, phosphoric acid, katana cleaner, and air abrasion. Shear bond strength (SBS) of resin composite bonded to the treated dentin using a universal adhesive was measured after thermocycling. Results Two-way ANOVA showed that hemostatic agent, cleansing protocol and their interaction has significant effect on SBS (p < 0.0001). Viscostat (10 ± 3.3 MPa) exhibited lower SBS than Viscostat Clear (16.2 ± 5.5 MPa). Acid etching (17.3 ± 7.3 MPa) showed higher SBS compared to Katana Cleaner (12.6 ± 4.7 MPa), water (12.1 ± 4.8 MPa) and air abrasion (10.8 ± 2 MPa). Conclusion The use of hemostatic agents can adversely affect the bond strength of universal adhesives to dentin. Phosphoric acid provided the best hemostatic agent-cleansing protocol while katana cleaner and air abrasion demonstrated inferior results.